Does the Admission Blood Pressure Associate with Short- and Long Term Outcome in Stroke Patients Treated with Thrombolysis? A Single Centre Study - L. Bentsen; C. Ovesen; A. F. Christensen; H. Christensen (International Journal of Hypertension)
Background. The association between outcome and elevated admission blood pressure (BP) remains uncertain in acute stroke patients. The aim of the present study was to examine the association between admission blood pressure and outcome in ischemic stroke patients treated with tissue plasminogen activator (tPA). Method. This study included patients treated with tPA within 4.5 hours after symptom onset. Four quartiles based on the admission BP values were defined. BP development of the first 12 hours was compared to outcome parameters defined as NIHSS 24 hours after tPA and mRS after 3 months. Results. 265 patients were included. A trend with worse short- and long-term outcome was present in the quartiles with the lowest and highest admission BP compared to the quartile with admission values at 140–160 mm Hg systolic. BP in quartile 1 was insignificantly decreased after 12 hours while the BP in quartiles 3 and 4 remained above recommended levels. Conclusion. Admission BP is associated with short- and long-term outcome after stroke. Low- or high-admission BP indicates cardiac comorbidity or preexisting hypertension, where close monitoring and further examinations are requested to prevent poorer outcome.